Miniaturization of UHF RFID tag antenna - Daud, Nor Hidayah (2015)
The main aim of this research is to reduce the size of RFID tag antenna using several miniaturization techniques. The tag antenna comprises of meandered lines and capacitive – tip loading integrated with two square split – ring resonators (S – SRRs). It was simulated using 3D full – wave electromagnetic simulator (CST Microwave Studio 2013) on FR4 epoxy substrate with the dielectric constant of 4.4, the loss tangent of 0.02 and the thickness of 1.53 mm. The UHF RFID chip used in this design was MURATA RFID Magicstrap LXMS31ACNA-010 chip with the impedance of 12 – j106.3 Ω at 921 MHz. The antenna has been designed to cover the frequency range in Malaysia, 919 MHz to 923 MHz. A parametric study of the proposed tag antenna was carried out in order to optimize the main effected parameters. The performance of the proposed tag were analysed in terms of return loss, antenna gain and maximum readable range. As compared to other passive UHF RFID tag antenna it is found that the size of antenna has achieved 61% reduction in size. It occupies the volume of 48 × 22 × 1.53 mm3. The measured read range of the proposed tag antenna is 4.60 m. Details of the proposed tag antenna design and measurement results are presented and discussed.